Hubungan Konsumsi Minuman Bersoda Dengan Timbulnya Gastritis Pada Remaja Di Dusun Selatan Desa Lemper Kecamatan Pademawu Kabupaten Pamekasan - Andri Priyoherianto; Fahmi Ardianti P; Panji Ratih Suci; Nabila Ayu Puspita Melati; Maghfiratul Maulidiah (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Gastritis is represent disease known in everyday life. Gastritis is often marked with painful in heart of queasy, vomiting, full satiety, stomach painful and etc. Soft drink one of the causes of stomach disorders because it has acid and caffeine. This research aims to knowing relation consume soft drink with incidence of gastritis at adolescent in Village South of Lemper District of Pademawu Regency of Pamekasan. Design of this research is case study with the technique of purposive sampling. Samples used totaled 89 adolescent men and women aged 12-18 years. Results of chi-square test show p-value=0.000 (p<0.05), have been got that relation consume soft drink with incidence of gastritis at adolescent in Village South of Lemper District of Pademawu Regency of Pamekasan. Shall all adolescent and society its participate actively to healthy live with consuming nutritious food and drink to prevent incidence of diseases such as gastritis.